2022
DOI: 10.7717/peerj.12907
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-victimization and its association with depression among Vietnamese adolescents

Abstract: Background Cyberbullying has become an alarming social issue, but little is known about its prevalence and consequences in many countries. This study investigated the prevalence of cyber-victimization and its association with depression among students in Ho Chi Minh City, Vietnam. Methods A cross-sectional study was conducted in 1,492 students from eight secondary schools and high schools in four urban and suburban areas. Multi-stage cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 54 In addition, students are in the stage of finding their identity so, in the intervention process, it is necessary to provide space so that students can still freely express what they feel. 55 This is supported by previous research which states that interventions to reduce cyberbullying against students need to pay attention to youth’s freedom of expression. 56 …”
Section: Discussionmentioning
confidence: 72%
“… 54 In addition, students are in the stage of finding their identity so, in the intervention process, it is necessary to provide space so that students can still freely express what they feel. 55 This is supported by previous research which states that interventions to reduce cyberbullying against students need to pay attention to youth’s freedom of expression. 56 …”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have already indicated that cyberbullying victims experience higher rates of depression [22,32,33] and anxiety [21,22,32,33]. Moreover, emotional problems vary in intensity and quality in adolescents who experience cyberbullying [34].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, among the articles included in the present systematic review, ten were conducted in Asia, that is, three in China [52,89,90], two in South Korea [91,92] and the remaining in Indonesia [93], Malaysia [94], Thailand [95], Turkey (eastern Anatolia) [96] and Vietnam [97]; three studies were conducted in European countries, i.e., Croatia [98], Finland [60] and Germany [99]; and the remaining three studies were carried out, respectively, in Australia [100], Canada [101] and Chile [102].…”
Section: Geographical Distribution Period and Methodologies Of Data C...mentioning
confidence: 99%
“…Regarding the selected studies' research design, four studies were longitudinal investigations [60,91,92,100], one was a randomized retrospective study [101], and the others were cross-sectional [52,89,90,[93][94][95][96][97][98][99]102].…”
Section: Geographical Distribution Period and Methodologies Of Data C...mentioning
confidence: 99%